Are Current Petroleum Fiscal Terms Sufficient to Drive Indonesia’s Energy Transition? A Systematic Review and Bibliometric Analysis - Krisdianto, Wahyu; Baihaqi, Imam; Gunarta, Ketut; Wibawa, Gede (International Journal of Energy Economics and Policy, 2025)
This study investigates whether Indonesia’s current petroleum fiscal terms are sufficient to drive the country’s energy transition while maintaining investment competitiveness. Using a systematic literature review (SLR), bibliometric analysis, and regulatory review, the research analyzed 673 studies out of 891 initial records, covering both Indonesian and international experiences with Production Sharing Contracts (PSC). The transition from Cost Recovery (CR) to Gross Split (GS) PSC simplified administrative processes and reduced fiscal verification burdens but also transferred greater risks to contractors, weakening investment attractiveness in marginal fields. Regulatory revisions from 2017 to 2024 introduced variable splits, Enhanced Oil Recovery (EOR) incentives, and provisions for Carbon Capture and Storage (CCS). However, frequent changes created policy uncertainty, undermining investor confidence at a time when long-term stability is critical. Bibliometric mapping highlights PSC regimes as a growing global research hotspot, with increasing connections to ESG, carbon pricing, and low-carbon pathways. Comparative evidence from 15 jurisdictions shows that hybrid and sliding-scale PSCs provide a better balance between fiscal stability and transition incentives. The findings conclude that Indonesia must adopt a simplified hybrid model that integrates EOR, CCS, and ESG-related incentives to align its upstream sector with long-term net-zero targets.